2021
DOI: 10.3389/fonc.2021.573798
|View full text |Cite
|
Sign up to set email alerts
|

Brain Microstructural Changes Associated With Neurocognitive Outcome in Intracranial Germ Cell Tumor Survivors

Abstract: BackgroundChildhood intracranial germ cell tumor (GCT) survivors are prone to radiotherapy-related neurotoxicity, which can lead to neurocognitive dysfunctions. Diffusion kurtosis imaging (DKI) is a diffusion MRI technique that is sensitive to brain microstructural changes. This study aimed to investigate the association between DKI metrics versus cognitive and functional outcomes of childhood intracranial GCT survivors.MethodsDKI was performed on childhood intracranial GCT survivors (n = 20) who had received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…The latter study also showed no changes in myelin water fraction, or ODI, NDI, or isotropic volume (Viso) derived from NODDI [ 115 ]. However, 11–12% decreases in mean kurtosis in the temporal lobe were measured in GM and WM in patients with nasopharyngeal carcinoma 1 week after RCTx with a further decrease to 34–39% after 1 year [ 116 ], and a decrease in WM, but not in GM was also found 1.2–12.2y after pediatric germ cell tumor [ 117 ]. An increase of radial kurtosis by 9% in NAWM was reported in testicular cancer survivors after CTx [ 118 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The latter study also showed no changes in myelin water fraction, or ODI, NDI, or isotropic volume (Viso) derived from NODDI [ 115 ]. However, 11–12% decreases in mean kurtosis in the temporal lobe were measured in GM and WM in patients with nasopharyngeal carcinoma 1 week after RCTx with a further decrease to 34–39% after 1 year [ 116 ], and a decrease in WM, but not in GM was also found 1.2–12.2y after pediatric germ cell tumor [ 117 ]. An increase of radial kurtosis by 9% in NAWM was reported in testicular cancer survivors after CTx [ 118 ].…”
Section: Resultsmentioning
confidence: 99%
“…One of the rare studies that looked at baseline values reported that memory recover at follow-up correlated both with pre-operative NDI and NDI recovery on follow-up [ 113 ]. In survivors of pediatric germ cell tumors, mean kurtosis correlated positively with Karnofsky’s performance score and IQ in several cortical regions, but not on the whole-brain level [ 117 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the improved survival, there are new challenges in the long-term management of childhood cancer survivors, who often require multi-disciplinary care, particularly for their medical and psychosocial sequalae that might adversely impact their quality of life [3]. Moreover, pediatric brain tumor survivors (PBTS) typically also have neurocognitive and behavioral problems [4][5][6][7][8][9]. Given that cranial radiotherapy (RT) is associated with a high risk of neurotoxicity in PBTS, many survivorship studies have focused on the cognitive outcomes of PBTS [8][9][10][11][12][13][14], but very few studies have investigated the neurobehavioral outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, pediatric brain tumor survivors (PBTS) typically also have neurocognitive and behavioral problems [4][5][6][7][8][9]. Given that cranial radiotherapy (RT) is associated with a high risk of neurotoxicity in PBTS, many survivorship studies have focused on the cognitive outcomes of PBTS [8][9][10][11][12][13][14], but very few studies have investigated the neurobehavioral outcomes.…”
Section: Introductionmentioning
confidence: 99%